Immune Dysregulation in Pediatric Common Variable Immunodeficiency: Implications for the Diagnostic Approach - Szczawińska-Popłonyk, Aleksandra; Ta̧polska-Jóźwiak, Katarzyna; Schwartzmann, Eyal; Popłonyk, Natalia (Frontiers in Pediatrics, 2022)
Infections and infectious complications are hallmarks of common variable immunodeficiency (CVID) and the leading cause of morbidity and mortality in affected patients at any age. However, the pediatric CVID is no longer perceived as a primary immunodeficiency associated solely with infectious manifestations but also autoimmune, allergic, lymphoproliferative, malignant disorders, and organ-specific immunopathology characterize the spectrum of non-infectious complications. In this study, we sought to determine the role of immune dysregulation and frequency of non-infectious sequelae in children affected with CVID. We also aimed at providing an insight into the pathogenesis of non-infectious complications and at delineating the diagnostic approach to pediatric CVID with immune dysregulation. An in-depth retrospective analysis of clinical manifestations and their correlations with selected immune parameters was performed in a group of 39 CVID children, followed by our pediatric immunology department. Whereas recurrent sinopulmonary infections were present in all (100%) of the children studied, an unexpectedly high rate of non-infectious disorders and immune dysregulation phenotypes were observed in as many as 32 (82.05%) patients, compared to infection-only phenotypes limited to 7 (17.95%) male patients. The most common inflammatory comorbidity was asthma, diagnosed in 21 (53.85%) patients. The second most frequent immune dysregulation group was autoimmune disorders, present in 18 (46.15%) of the children studied with a high rate of autoimmune thyroiditis in as many as 10 (25.64%) of the CVID affected children. Lymphoproliferation was seen in 14 children (35.90%) and among them, lymphadenopathy occurred in 9 (23.08%) and granulomatous lymphocytic interstitial lung disease (GLILD) in 7 (17.95%) cases. Finally, malignancies occurred in two female patients (5.13%), papillary thyroid cancer in the first one and T-cell lymphoblastic leukemia in the other one. The most prominent abnormalities in the B and T cell compartment contributing to complex immune deficiency and immune dysregulation phenotypes were seen in the autoimmunity group, showing significant reductions in the switched memory B cell, naive T helper cell, and regulatory T cell subsets. Herein we document a previously unreported high rate of immune dysregulation in pediatric CVID as a clinical and diagnostic challenge with the variability of defects in the humoral and cellular immune responses.